A comparative Study of the Kinetics of Hydrolysis of the Methyl Derivatives of Salicyalnil - Prabhu, D.V.; Laxmeshwar, N.B. (Asian Journal of Chemistry, 2010)
A comparative study of the hydrolysis of the methyl derivatives of salicylanil has been done in the pH range 3.57–12.65 at 35ºC. The reaction mechanisms in acidic, neutral and basic media have been discussed on the basis of steric hindrance, inductive, mesomeric and resonance effects. The rates of hydrolysis of the Schiff bases have been correlated with their proton dissociation constants.